(m-3)(m+3)-(m+7)(m+7)=

Simple and best practice solution for (m-3)(m+3)-(m+7)(m+7)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (m-3)(m+3)-(m+7)(m+7)= equation:


Simplifying
(m + -3)(m + 3) + -1(m + 7)(m + 7) = 0

Reorder the terms:
(-3 + m)(m + 3) + -1(m + 7)(m + 7) = 0

Reorder the terms:
(-3 + m)(3 + m) + -1(m + 7)(m + 7) = 0

Multiply (-3 + m) * (3 + m)
(-3(3 + m) + m(3 + m)) + -1(m + 7)(m + 7) = 0
((3 * -3 + m * -3) + m(3 + m)) + -1(m + 7)(m + 7) = 0
((-9 + -3m) + m(3 + m)) + -1(m + 7)(m + 7) = 0
(-9 + -3m + (3 * m + m * m)) + -1(m + 7)(m + 7) = 0
(-9 + -3m + (3m + m2)) + -1(m + 7)(m + 7) = 0

Combine like terms: -3m + 3m = 0
(-9 + 0 + m2) + -1(m + 7)(m + 7) = 0
(-9 + m2) + -1(m + 7)(m + 7) = 0

Reorder the terms:
-9 + m2 + -1(7 + m)(m + 7) = 0

Reorder the terms:
-9 + m2 + -1(7 + m)(7 + m) = 0

Multiply (7 + m) * (7 + m)
-9 + m2 + -1(7(7 + m) + m(7 + m)) = 0
-9 + m2 + -1((7 * 7 + m * 7) + m(7 + m)) = 0
-9 + m2 + -1((49 + 7m) + m(7 + m)) = 0
-9 + m2 + -1(49 + 7m + (7 * m + m * m)) = 0
-9 + m2 + -1(49 + 7m + (7m + m2)) = 0

Combine like terms: 7m + 7m = 14m
-9 + m2 + -1(49 + 14m + m2) = 0
-9 + m2 + (49 * -1 + 14m * -1 + m2 * -1) = 0
-9 + m2 + (-49 + -14m + -1m2) = 0

Reorder the terms:
-9 + -49 + -14m + m2 + -1m2 = 0

Combine like terms: -9 + -49 = -58
-58 + -14m + m2 + -1m2 = 0

Combine like terms: m2 + -1m2 = 0
-58 + -14m + 0 = 0
-58 + -14m = 0

Solving
-58 + -14m = 0

Solving for variable 'm'.

Move all terms containing m to the left, all other terms to the right.

Add '58' to each side of the equation.
-58 + 58 + -14m = 0 + 58

Combine like terms: -58 + 58 = 0
0 + -14m = 0 + 58
-14m = 0 + 58

Combine like terms: 0 + 58 = 58
-14m = 58

Divide each side by '-14'.
m = -4.142857143

Simplifying
m = -4.142857143

See similar equations:

| 8(x+8)-21= | | 11(5a)= | | 2x-5x+7x-8x= | | 8(t-2)=3(t-9) | | 3k=(-0.857142) | | -13r+10=5r-46 | | 4w-9=0 | | 20x+2=5(4x+1)-x+5 | | 10y=-5y | | 0.33(p+1)=0.5(p-2) | | 5x+11=51 | | x=7x | | n*5-10=-25 | | 3x-48x=0 | | 7m+49= | | (r-5)=-6 | | 23=2x | | (2y-3)(y+5)=0 | | y=1.5x-1 | | 25x+3=5(5x+1)-x+4 | | x+3x^2-2=0 | | y=-3.5x-2 | | y=3.5x-1 | | y=6x^2-9 | | (-8x)-4=36 | | 5=3x-4 | | 2=4m+8 | | -19=3x-4 | | 3x+8x=-132 | | (2x+-65)=15x | | (2x+-65)=15 | | 4x+6=2x+16 |

Equations solver categories